APPROACHES TO ENHANCING THE FINANCING SYSTEM FOR HOUSING PROVISION TO THE POPULATION - Abdukayumov Xumoyunmirzo Giyosbek o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Housing provision is one of the most essential components of social and economic development. Adequate housing ensures not only physical comfort but also social stability, improved health, and human capital formation. In Uzbekistan, housing policy has been given great importance during the past decade as the country continues its process of modernization and urbanization. The government has implemented numerous programs to expand access to affordable housing, develop mortgage markets, and attract private investment. However, despite significant achievements, the financing mechanisms for housing provision still require further improvement to meet the growing needs of the population and to adapt to market realities.